Hegemoni Barat dalam Kebijakan Pemuda ASEAN: Analisis Wacana Kritis atas Paradigma Generasional dalam AMMY (1992–2024) dan AMMY+3 (2007–2023) - Mahatma Aditya Mikaila (Universitas Gadjah Mada, 2025)
This study critically examines how ASEAN’s policies on youth issues reproduce development narratives rooted in Western hegemonic ideologies. The novelty of this research lies in its focus on the ideological construction of youth within ASEAN’s policy discourse, differing from previous studies that primarily view youth as neutral subjects of development. Employing (Fairclough’s 2023) Critical Discourse Analysis and (Escobar’s 1995) decolonization framework, the study analyzes policy texts from the ASEAN Ministerial Meeting on Youth (AMMY) and ASEAN Ministerial Meeting on Youth +3 (AMMY+3) to uncover the underlying power structures and meanings embedded in ASEAN’s development agenda.The findings reveal that youth within ASEAN discourse are constructed through the “Instrumentalization of Youth,” where they are positioned primarily as objects and beneficiaries of development rather than as autonomous actors or decision-makers. The narratives emphasize youth as economic and social assets who contribute to regional stability and productivity, while concerns related to equity, participation, and social justice remain marginalized. The results demonstrate ASEAN’s continued adherence to Western development paradigms prioritizing economic growth, employability, and resilience, often overlooking local contexts, cultural diversity, and political constraints. The study concludes by arguing for a transformative, inclusive, and justice-oriented policy framework recognizing young people as rights-bearing individuals capable of shaping ASEAN’s social and political future.